1997
DOI: 10.1111/j.1365-2621.1997.tb02118.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties of spray‐dried and freeze‐dried faba bean protein concentrates

Abstract: A protein concentrate from faba bean seeds was prepared by isoelectric precipitation and spray-dried. Its functional properties were measured and the results obtained were compared to those from another concentrate prepared by the classical freeze-drying technique. The functional properties were found to be indistinguishable. However, the protein solubility profile was different depending on the preparation technique. Some antinutritional factors (trypsin inhibitors, tannins and phytates) were also analysed. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 19 publications
0
14
0
2
Order By: Relevance
“…Segundo Damodaran (1997), na maioria das proteínas ocorre mínima solubilidade no pH isoelétrico (pH 4-5), onde a repulsão eletrostática e a hidratação iônica são mínimas e a interação hidrofóbica entre as superfícies não polares é máxima. Resultados semelhantes foram encontrados em concentrado proteico de feijão fava novo e concentrados proteicos de feijão carioca novo e armazenado por Otegui et al (1997) e Donadel e Prudêncio-Ferreira (1999).…”
Section: Solubilidade Das Proteínas E Capacidade De Absorção De áGua unclassified
See 1 more Smart Citation
“…Segundo Damodaran (1997), na maioria das proteínas ocorre mínima solubilidade no pH isoelétrico (pH 4-5), onde a repulsão eletrostática e a hidratação iônica são mínimas e a interação hidrofóbica entre as superfícies não polares é máxima. Resultados semelhantes foram encontrados em concentrado proteico de feijão fava novo e concentrados proteicos de feijão carioca novo e armazenado por Otegui et al (1997) e Donadel e Prudêncio-Ferreira (1999).…”
Section: Solubilidade Das Proteínas E Capacidade De Absorção De áGua unclassified
“…Resultados semelhantes foram encontrados por Donadel e Prudêncio-Ferreira (1999) ao avaliarem as propriedades funcionais de concentrado proteico de feijão comum, variedade carioca, envelhecido. A concentração mínima de dispersão para formação de gel observada neste trabalho foi maior do que as encontradas na literatura para isolados e concentrados de feijão 'mung' (COFFMANN; GARCIA, 1977); tremoço (KING; AGUIRRE; PABLO, 1985) e feijão fava (OTEGUI et al, 1997), novos.…”
Section: Capacidade De Formação De Gelunclassified
“…Consequently, the functional properties of the materials might also be affected (Chinprahast, Jantawat, & Kristavee, 1995;Otegui et al, 1997). The physical state of an amorphous matrix greatly influences stability and affects rates of both physical and chemical changes during processing and storage (Buera & Karel, 1995;Champion, Le Meste, & Simatos, 2000;Eichner, 1981;Karmas, Buera, & Karel, 1992;Kim, Saltmarch, & Labuza, 1981;Roos, Karel, & Kokini, 1996;Roudaut, Simatos, Champion, Contreras-Lopez, & Le Meste, 2004;Slade & Levine, 1991).…”
Section: Introductionmentioning
confidence: 97%
“…Those structural and morphological differences had significant effects on the functional properties of food proteins (Otegui et al, 1997;Rahman, Al-Amri, & Al-Bulushi, 2002). Changes in functional properties of globular proteins during freezedrying and spray-drying, e.g., egg albumen, whole egg and yolk (Ayadi, Khemakhem, Belgith, & Attia, 2008;Galyean & Cotterill, 1979), hen egg ovalbumin (Kitabatake, Indo, & Doi, 1989), porcine blood plasma (Agyare, Addo, & Xiong, 2009) and faba bean protein (Cepeda, Villarán, & Aranguiz, 1998;Otegui et al, 1997), have been extensively reported. As for wheat gluten protein which has a network structure, Linarès, Larré, and Popineau (2001a) found that drying process induced no significant modification of molecular size distribution, hydrophobicity, and solubility of wheat gluten protein, and the interfacial properties of soluble peptides from freeze-and spray-dried samples were equivalent.…”
Section: Introductionmentioning
confidence: 98%